Phenomenological Study of Emergency Ambulance Transport Referral Process at RSUD Raden Mattaher Jambi Province - Ravia Gustina; Andi Subandi; Dini Rudini (West Science Interdisciplinary Studies, 2024)
As a regional general hospital, Raden Matthaer Regional Hospital is of course the main destination for people to go for treatment. Limited facilities are one of the obstacles to patient service, quite a few patients who have received treatment at Raden Mattaher Hospital are referred to other hospitals to continue treatment. Referrals are not only made within the city but also to hospitals outside the city. Referral of patients to hospitals outside the city when services are not available at hospitals in Jambi. During the referral process, of course, ambulance transportation is required. Using an ambulance also depends on the patient's needs. The aim of this research is to analyze the referral process for emergency ambulance transportation at Raden Mattaher Regional Hospital, Jambi Province.  This research is descriptive qualitative research. There were four participants. The verbatim transcript interview results were processed and produced 3 main themes, namely the referral process, transportation and Integrated referral information system. From this research it can also be seen how the referral process, use of ambulances, and use of SISRUTE are.